Tempted : a House of Night novel - Cast, P. C.; Cast, Kristin (Cast, P. C. House of night, 2009)
Zoey Redbird, High Priestess-in-training, finds herself juggling three guys--one of which is so into protecting her that he can sense her emotions. Meanwhile the dark force lurking in the tunnels under the Tulsa Depot is spreading, and only Zoey has the power to stop the evil immortal Kalona who is behind it. Will Zoey have the courage to chance losing her life, her heart, and her soul?